Recurrent Adolescent Giant-Cell Tumor of the Scaphoid: Scaphoid Excision with Intracarpal Fusion after Failed Curettage and Bone Grafting - Chris Hoedt; Gabriel S. Makar; Christina J. Gutowski; Thomas Holdbrook; Tae Won B. Kim; David A. Fuller (Case Reports in Orthopedics)
We present a case of the giant-cell tumor of bone in the scaphoid of a 17-year-old female. Imaging revealed an expansile lytic lesion of her scaphoid, and the diagnosis was confirmed with open biopsy. She was treated with curettage and iliac crest bone graft, in an effort to spare reconstruction of her wrist. After one year, she developed increasing tightness and pain. Local recurrence was apparent on radiographs, and CT revealed increased lucency with bony destruction in the area of prior excision. She was successfully treated, without recurrence to date, with complete scaphoid excision and a four-corner wrist fusion. Local recurrence of the giant-cell tumor of bone is high, especially in carpal bones. When treating patients with advanced lesions, more aggressive initial options should be considered.